2011
DOI: 10.1159/000329862
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Dementia: A Study from a Memory Clinic in India

Abstract: Background: The clinical syndrome of dementia consists of several subtypes that are distinct in their etiology, clinical profile, management, and outcome. Limited specialized services are available for dementia patients in India. We report the profile of dementia subtypes from a clinic-based dementia registry in India. Methods: Consecutive dementia patients were investigated with clinical evaluation, neuropsychological tests modified for local use, and brain imaging. Results: In 347 consecutive dementia patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 64 publications
(80 reference statements)
8
58
3
Order By: Relevance
“…However, to our knowledge, there is no other database in the world with a higher number of patients with different diagnosed dementia disorders. The prevalence of DLB and FTD was in a similar range as reported in previous studies [3,32,33,34]. However, 10% of the dementia patients were diagnosed with unspecified dementia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, to our knowledge, there is no other database in the world with a higher number of patients with different diagnosed dementia disorders. The prevalence of DLB and FTD was in a similar range as reported in previous studies [3,32,33,34]. However, 10% of the dementia patients were diagnosed with unspecified dementia.…”
Section: Discussionsupporting
confidence: 85%
“…The diagnosis of unspecified dementia (International Classification of Diseases, ICD-10 code F03) is based on a cognitive disorder with dementia but with unknown aetiology, or that the investigations aimed to determine aetiology were not performed. There is limited research on comparisons between all different dementia disorders [5], maybe due to lack of sufficiently large databases.…”
Section: Introductionmentioning
confidence: 99%
“…One third had vascular aetiology, reflecting the high prevalence of cardiovascular disease in India [20 ]and consistent with studies that have demonstrated the association between vascular disease and cognitive impairment [40]. Vitamin B 12 deficiency was an important reversible cause of cognitive dysfunction, a reflection of the frequent occurrence of vitamin B 12 deficiency-related dementia in India [41].…”
Section: Discussionmentioning
confidence: 53%
“…Patient age, gender, educational status in years, occupational status as classified by the National Classification of Occupations - 2004 [23], history of stroke and the presence of vascular risk factors were recorded for all subjects according to a structured protocol [20]. All participants were evaluated using the Mini-Mental State Examination (MMSE) [24], Addenbrooke's Cognitive Examination-Revised (ACE-R), adapted and translated into Telugu and Hindi [20,25],and the Clinical Dementia Rating Scale (CDR) [26]. Depression and anxiety were scored using the Hospital Anxiety and Depression Scale (HADS) [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation